Two-Stage Detectors with Multiple Energy Detectors and Adaptive Double Threshold in Cognitive Radio Networks. (24th August 2013) - Bagwari, Ashish; Tomar, Geetam Singh
Abstract : Cognitive radio (CR) is a regulated technique for opportunistic access of idle resources. In CR, spectrum sensing is one of the key functionalities. It is used to sense the unused spectrum in an opportunistic manner. In this paper, we have proposed two-stage detectors for spectrum sensing in cognitive radio networks (CRN). The first stage consists of multiple energy detectors (MED), where each energy detector (ED) is having single antenna with fixed threshold (MED_FT) for making a local binary decision, and if required, the second stage comprised of ED with adaptive double threshold (ED_ADT) is invoked. The detection performance of the proposed scheme is compared with cyclostationary-based sensing method and adaptive spectrum sensing scheme. Numerical results show that the proposed scheme improves detection performance and outperforms the cyclostationary-based sensing method and adaptive spectrum sensing by 12.3% and 14.4% at signal to noise ratio (SNR) setting of as low as −8 dB, respectively. Performance was also measured in terms of sensing time. It is shown that the proposed scheme yields smaller sensing time than cyclostationary detection and adaptive spectrum sensing scheme in the order of 4.3 ms and 0.1 ms at −20 dB SNR, respectively.